Ethical Use of ChatGPT in the Context of Leadership and Strategic Decisions - Abdul Basir; Erlinda Dwi Puspitasari; Cindy Chintya Aristarini; Pebri Defi Sulastri; Abu Muna Almaududi Ausat (Jurnal Minfo Polgan, 2023)
The development of AI has had a significant impact on various aspects of human life, including in the fields of communication and decision-making. One popular example of AI is ChatGPT, a generative language model designed to interact and generate human-like text. While ChatGPT provides great potential in facilitating communication and decision-making, its presence also poses ethical challenges that need to be considered. This research aims to explore the ethical issues that arise in the use of ChatGPT in the context of leadership and decision-making, and formulate an ethical framework that can guide the responsible and beneficial practice of using ChatGPT. The current research type is qualitative. Data collection techniques include listening and recording important information to conduct data analysis through data reduction, data display, and conclusion drawing. The study results show that the ethical use of ChatGPT in the context of leadership and strategic decision-making involves complex and important considerations related to transparency, fairness, privacy, long-term impact considerations, and risk management. While ChatGPT can provide significant benefits, it also poses ethical challenges that need to be addressed.